A Postcolonial Study of Native American Marginalization in Wapiti Reservation, Red Dead Redemption 2 - Salsabila, Hanung Falakh; Prihatika, Yusrina Dinar (Universitas Pahlawan Tuanku Tambusai, 2026)
Although Red Dead Redemption 2 has been widely praised for its historical realism and narrative depth, limited studies have critically examined how Indigenous voices are represented and whether they can truly “speak” within its narrative framework. This study analyzes the representation of Indigenous oppression through the fictional Wapiti tribe in the video game Red Dead Redemption 2 (RDR2). The tribe mirrors real Native American experiences of forced displacement, military violence, and cultural erasure. Using Gayatri Spivak’s postcolonial concept of the subaltern and a qualitative descriptive method, the research examines six key missions depicting the Wapiti tribe’s suffering and resistance. Data were collected through gameplay observation, including screenshots, dialogue transcripts, and narrative field notes. The analysis applies Spivak’s question of whether the subaltern can truly “speak” to explore how Indigenous voices are mediated and silenced within the game’s narrative framework. The findings reveal that RDR2 portrays both structural and symbolic oppression, where the Wapiti Reservation operates as a postcolonial space of erasure, surveillance, and control. Overall, this study contributes to American Studies by highlighting how digital media reproduces colonial ideologies and marginalizes Indigenous identity within contemporary popular culture.